2015
DOI: 10.5688/ajpe797103
|View full text |Cite
|
Sign up to set email alerts
|

Flipping Content to Improve Student Examination Performance in a Pharmacogenomics Course

Abstract: Objective. To develop, implement, and evaluate active learning in a flipped class to improve student examination performance in the genetic foundations of pharmacogenomics. Design. The flipped classroom model was adopted in which a guided-inquiry learning activity was developed and conducted to complement recorded, previously viewed didactic lectures. The activity was constructed to focus on critical thinking and application of core principles of genetic crosses and pedigree analysis. A combination of independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 8 publications
0
32
0
3
Order By: Relevance
“…6 Similar results have been established from various studies assessing the impact of flipped educational and assessment models in science and pharmacy undergraduate courses worldwide. 4,7,[10][11][12][13] Despite this growing interest in the flipped classroom approach and the promising results obtained in terms of students' performance and satisfaction in the pharmacy curriculum, 4,[11][12][13] this model has not…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…6 Similar results have been established from various studies assessing the impact of flipped educational and assessment models in science and pharmacy undergraduate courses worldwide. 4,7,[10][11][12][13] Despite this growing interest in the flipped classroom approach and the promising results obtained in terms of students' performance and satisfaction in the pharmacy curriculum, 4,[11][12][13] this model has not…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…Previous studies revealed that the teaching model of the flipped classroom notably enabled students to acquire knowledge, since the learning efficiency of the inverted classroom was more enhanced than that of the lecture-based instruction method [3,20,27]. The first documented use of the flipped classroom in teaching medical students was published in 2012 by Prober et al [28].…”
Section: Discussionmentioning
confidence: 99%
“…Somit scheinen sich die allgemeinen lerntheoretischen Überlegungen zu bestätigen, wonach die schüleraktivierende und selbstbestimmungsfördernde Art des Lernens im Flipped Classroom zu einem höheren Lernzuwachs führt. Doch eine ganze Reihe von Studien stellt auch fest, dass die Leistungen von Lernenden im Flipped Classroom sich nicht signifikant unterschieden von denen der Lernenden in traditionellem Unterricht (Bell 2015;Bishop 2013;Findlay-Thompson & Mombourquette 2014;Gillette et al 2018;Jensen et al 2015;Johnson & Renner 2012;Lape et al 2014;Lewis et al 2018;Marlowe 2012;Munson & Pierce 2015;Zheng et al 2014 Ein Urteil über die Lernwirksamkeit des Flipped Classroom muss sich am Unterricht messen, mit dem er verglichen wird. Der Begriff »traditioneller Unterricht« ist diffus und bezeichnet in vielen Studien unterschiedliche Formen des Unterrichtens -von der klassischen Vorlesung ohne jede Aktivität der Lernenden bis zu fragend-entwickelndem Unterricht, der mit einem hohen Grad an Schüleraktivität gestaltet werden kann.…”
Section: Probleme Im Flipped Classroomunclassified
“…Die Vielzahl der Arten, wie Flipped Classroom im Unterricht eingeführt und umgesetzt werden kann, erklärt die Bandbreite an Ergebnissen, die die Studien auf diesem Gebiet zu Tage förderten. So gibt es auch viele Studien, in denen es keine signifikanten Unterschiede in den Lernleistungen im Flipped Classroom und traditionellen Lehrformaten gab (Bell 2015;Bishop 2013;Findlay-Thompson & Mombourquette 2014;Jensen et al 2015;Johnson & Renner 2012;Lape et al 2014;Marlowe 2012;Munson & Pierce 2015;Zheng et al 2014 Krapp 2002) und auch schon auf Zeitskalen von Monaten (Daniels 2008) und Wochen (Weber 2003;Winkelmann 2013…”
Section: Hypothese 1a: Lernleistungunclassified
See 1 more Smart Citation